Underpricing Stock Level of Sharehold in Stock Company Doing Income Smoothing Procedures at the Price Offer of Prime Stock in Indonesia Stock Exchange - Kartikawati, Theresia Siwi; Yuliana, Elsa Sari; Tarmizi, Tashadi (International Journal of Economics and Financial Issues, 2019)
This study aims to analyze the effect of firm size, profitability, financial leverage to the level of underpricing in companies that are detected to perform income smoothing practices at the time of initial public offering in Indonesia Stock Exchange period 2012-2014. Based on the results of data analysis, partial testing shows that firm size variables, return on assets and financial leverage have no significant effect on the level of underpricing of shares. The result of the research also shows that there is no significant difference between level of underpricing between companies indicated to practice income smoothing with companies that are not indicated to practice income smoothing. Keywords: income smoothing, underpricing, stock exchange JEL Classifications: G32, G38, G28 DOI: https://doi.org/10.32479/ijefi.7614